Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 2:
a; 17 - 11 - (-39)
= 17 - 11 + 39
= 6 + 39
= 45
b; 125 - 4[ 3 -7 .(-2)]
= 125 - 4.[3 + 14]
= 125 - 4.17
= 125 - 68
= 57
bài1:a
-3 + 12
= 12 - 3
= 9
b)(-24) : 8 = -3
c)-9 - 13
= -9 + (-13)
=-(9 + 13)
= -22
\(-10< x< 8\)
\(\Rightarrow x\in\left\{-9;-8;...;7\right\}\)
\(x=-9+\left(-8\right)+...+7\)
\(\Rightarrow x=\left(-9\right)+\left(-8\right)=-17\)
P/s: Các câu còn lại tương tự ((:
a, \(-6x=18\)
\(\Rightarrow-x=3\)
\(\Rightarrow x=-3\)
b, \(2x-\left(-3\right)=7\)
\(2x+3=7\)
\(\Rightarrow2x=4\)
\(\Rightarrow x=2\)
c, \(\left(x-5\right)\left(x+6\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x-5=0\\x+6=0\end{cases}\Rightarrow\orbr{\begin{cases}x=5\\x=-6\end{cases}}}\)
Bài 1:
a) \(33^{2x}:11^{2x}=81\)\(\Leftrightarrow\left(33:11\right)^{2x}=81\)
\(\Leftrightarrow3^{2x}=3^4\)\(\Leftrightarrow2x=4\)\(\Leftrightarrow x=2\)
Vậy \(x=2\)
b) \(\frac{x}{-5}=\frac{4}{21}\)\(\Leftrightarrow21x=-20\)\(\Leftrightarrow x=\frac{-20}{21}\)
Vậy \(x=\frac{-20}{21}\)
Bài 2:
\(A=\frac{1+3^4+3^8+3^{12}}{1+3^2+3^4+3^6+3^8+3^{10}+3^{12}+3^{14}}\)
\(=\frac{1+3^4+3^8+3^{12}}{\left(1+3^4+3^8+3^{12}\right)+\left(3^2+3^6+3^{10}+3^{14}\right)}\)
\(=\frac{1+3^4+3^8+3^{12}}{\left(1+3^4+3^8+3^{12}\right)+3^2.\left(1+3^4+3^8+3^{12}\right)}\)
\(=\frac{1+3^4+3^8+3^{12}}{\left(1+3^4+3^8+3^{12}\right).\left(1+3^2\right)}=\frac{1}{1+3^2}=\frac{1}{1+9}=\frac{1}{10}\)
\(33^{2x}:11^{2x}=81\)!
\(\left(33:11\right)^{2x}=81\)
\(3^{2x}=81\)
\(3^{2x}=3^4\)
\(2x=4\)
\(x=4:2\)
\(x=2\)
vậy \(x=2\)
\(\frac{x}{-5}=\frac{4}{21}\)
x.21=-5.4
x.21=-20
x=-20:21
\(x=-\frac{20}{21}\)
vậy \(x=-\frac{20}{21}\)
Bài 1:
|-2012| + 2.(|+12| - 120)
= 2012 + 2.(12 - 1)
= 2012 + 2.11
= 2012 + 22
= 2034